Iron absorption and oxidant stress during erythropoietin therapy in very low birth weight premature infants: a cohort study - Aziz Khalid; Andrews Wayne L; Friel James K; Serfass Robert E (BMC, 2005)
Abstract Background Iron supplementation may be associated with oxidative stress particularly in premature infants. Our purpose was to examine 1) early supplemental iron during treatment with erythropoietin (EPO) and oxidative stress; 2) enhanced iron absorption during EPO in those infants receiving human milk. Therefore, we determined the effect of erythropoietin plus supplemental iron intakes (4 mg/kg/d) on antioxidant status and iron incorporation. Methods Ten very-low-birth-weight infants who were enterally fed and receiving either human milk or formula were followed for 4 weeks during erythropoietin therapy; blood and urine were collected at 3 times; baseline, 2 and 4 weeks later. Once oral feeds commenced the study protocol was initiated. After baseline blood collection, a dose of Fe57 was administered. Two weeks later, a dose of Fe58 was administered as ferrous chloride to determine the effect of human-milk or formula on iron incorporation into RBCs. Results Infants started the study at 35 ± 13 days. Incorporation of isotope into RBCs did not differ between formula fed for Fe57 (mean incorporation 8 ± 2.9 n = 3) compared to human-milk fed infants (8.7 ± 5 n = 7) nor for Fe58 (6 ± 2.7 n = 3 vs. 8.6 ± 5 n = 7). Tissue damage measured by malondialdehyde in plasma and F-2 - isoprostanes in urine, did not differ by feed or over time. Neither ability to resist oxidative stress/nor RBC superoxide dismutase differed according to feed or over time. Conclusion Data suggest that during erythropoietin therapy antioxidant defence in VLBW infants are capable of dealing with early supplemental iron during treatment with EPO.